Salivary human papilloma virus detection in head & neck cancers in Malaysia : a multicentre study - A/L Ramalinggam, Ganesh (2015)

(untitled)
Introduction: A steady rise in incidence of oral cavity and oropharyngeal cases especially among young males with no history of tobacco smoking or alcohol consumption have given rise to a new risk factor, namely human papillomavirus (HPV). The role of HPV in these cancers are evidenced in many studies. Local studies on this trend are scarce and HPV prevalence among local population has not been undertaken before. Objectives: This study was conducted to determine prevalence and association of HPV among oral cavity/oropharyngeal cancer patients and healthy local population. It also aims to identify the association of HPV and risk factors such as smoking, alcohol consumption, betel nut chewing and family history of cancer. Methodology: This is a case-control study involving a test group (oral cavity and oropharyngeal cancer patients) and a control group (healthy individuals). HPV status is tested via salivary rinse samples collected using Diacarta Quantivirus® HPV salivary rinse collection kit and processed using Diacarta Quantivirus® HPV E6/E7 RNA assay. Data collection and salivary sample collection were done with informed consent from July 2013 till June 2014 involving patients from 3 different institutions to achieve optimal sample size. Results: This study involves 58 subjects, consisting of 29 test subjects who are patients with oral cavity cancer and 29 control subjects who are healthy. There were no patients with oropharyngeal cancer in the test group. HPV prevalence was found to be 55.1% among test subjects and 3.4% among control subjects. This was found to be significant (p=0.001) with odds ratio of 33.90 (95% CI 3.88, 295.99). Among the risk factors, smoking habit was seen in 51.2% of test subjects and 13.8% of control subjects. This association was found to be significant (p=0.041) with odds ratio of 4.36 (95% CI 1.06, 17.86). Multicolinearity and interaction term were checked and none found. Alcohol consumption was found to be insignificant (p=0.241) in this study. Family history of cancer was seen in 31.0% of subjects in test group and 6.9% in control group. This was found to be significant (p=0.019) with an odds ratio of 6.08 (95% CI 1.181, 31.244). Conclusion: HPV prevalence among oral cavity patients was found to be high and this pivotal result demonstrates HPV infection is now an established risk factor in this country. Smoking habit was also found to be a significant risk factor among these patients and did not interact or confound the factor of HPV infection.